An overview on the importance of surface modification by TIG and lasers incorporating carbides and their relations to wear behaviours - Md Idriss, Ahmed Nazrin; Kasolang, Salmiah; Md. Abdul, Maleque; Md Nasir, Ramdziah (Malaysian Tribology Society, 2021)
Surface modification is a technique via induction of high energy input to produce a hard resilient thin layer on the surface of the weak substrate. Despite by lasers capable to produce surface modified structures, their vehement cost of manufacturing is not comparable to the TIG torch melting technique which can develop similar quality surface with less cost. To the extent of author’s knowledge, the constant degradation of metal surfaces during friction are most likely to use wear test analysis in order to assess the durability of the coatings. This work takes another important step in discussing the importance of surface modifications at high energy inputs via incorporating reinforcing material by improvising micro-hardness property and finding relationship with wear behavior of the surface modified materials. Several issues on the wear behaviour of coatings mainly from the effect of surface hardness and those without coating with regard to their applications were highlighted. Periodical wear which the author’s enthusiast as a fresh niche area of wear wasn’t that much being explored; hence, explanation was extended at the end of this paper.